Activities of dl-α-Difluoromethylarginine and Polyamine Analogues against Cryptosporidium parvum Infection in a T-Cell Receptor Alpha-Deficient Mouse Model - Yarlett, Nigel (American Society for Microbiology, 2007)
The in vivo effectiveness of a series of conformationally restricted polyamine analogues alone and selected members in combination with dl-α-difluoromethylarginine against Cryptosporidium parvum infection in a T-cell receptor alpha-deficient mouse model was tested. Polyamine analogues were selected from the extended bis(ethyl)-sym-homospermidine or bis(ethyl)-spermine backbone having cis or trans double bonds at the center of the molecule. The cis isomers were found to have significantly greater efficacy in both preventing and curing infection in a mouse model than the trans polyamine analogues when tested in a T-cell receptor alpha-deficient mouse model. When tested in combination with dl-α-difluoromethylarginine, the cis-restricted analogues were found to be more effective in preventing oocyst shedding. This study demonstrates the potential of polyamine analogues as anticryptosporidial agents and highlights the presence of multiple points in polyamine synthesis by this parasite that are susceptible to inhibition resulting in growth inhibition.